Transformasi Regulasi Equity Crowdfunding melalui POJK Nomor 57/POJK.04/2020 terhadap Perlindungan Hukum PT Santara Daya Inspiratama - Belva Syahda Mahardika (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study discusses the transformation of equity crowdfunding regulations in Indonesia through Financial Services Authority Rehis study discusses the transformation of equity crowdfunding regulations in Indonesia through Financial Services Authority Regulation (POJK) Number 57/POJK.04/2020, with a focus on legal protection for PT Santara Daya Inspiratama as one of the providers of information technology-based crowdfunding services. The background of this research is based on the need for alternative funding schemes for Micro, Small, and Medium Enterprises and startups, which have difficulty in obtaining access to funding from conventional financial institutions. The research method used is normative juridical with an analytical approach to related laws and regulations and literature studies as primary and secondary data sources. This study examines the differences in regulations between POJK No. 37/POJK.04/2018 and POJK No. 57/POJK.04/2020, as well as their impact on the implementation mechanism of equity crowdfunding in Indonesia. The results of the study show that although POJK No. 57/POJK.04/2020 provides a stronger legal basis for the protection of investors and issuers, there is still ambiguity in its implementation, especially regarding the obligation to register securities at the Indonesian Central Securities Depository (KSEI) for non-limited liability company issuers. The case of sanctions against PT Santara illustrates this regulatory challenge, where the provisions are not fully in accordance with the characteristics of issuers in the form of Commanditaire Vennootschap (CV) or individuals. Therefore, further evaluation is needed to ensure that the regulation can provide optimal legal protection and support an inclusive and sustainable equity crowdfunding ecosystem in Indonesia.